Effect of enzyme compositions on the rheological properties of bread dough enriched in buckwheat flour - Liu, Wenjun; Brennan, Margaret; Tu, Dawei; Brennan, Charles; Huang, Wei (Food Science and Technology, 2023)
Buckwheat is a good source of dietary fibre, protein and minerals, which has many beneficial effects on human health. However, previous research has illustrated that the addition of buckwheat has detrimental effects on the dough rheology and final products quality. Thus, the objective of this study was to investigate the effects of α-amylase (6 and 10 ppm), xylanase (70 and 120 ppm) and cellulase (35 and 60 ppm) on the rheological properties of bread dough incorporated with buckwheat flour. The mixing property of dough was measured by using a DoughLAB. The results indicated that the addition of single enzyme decreased water absorption, development time, stability, extensibility and stickiness, whereas increased softening, MTI and resistance to extension. Compared to the single enzyme, the enzyme compositions showed lower development time, water absorption and stability, and higher softening, MTI, resistance to extension and extensibility. As a result, enzyme compositions were more efficient than the single enzyme due to the synergistic effect of α-amylase, xylanase and cellulase. Practical Application: This work investigates how the single enzyme and combined enzymes influence the rheological properties of buckwheat dough during bread making. It has a widespread practical application in baking industry.